Socio-territorial conflicts: artisanal fishing as a common good in the Valdés Peninsula, Argentina (Polis (Santiago), 2020)
The article studies the participation of artisanal fishermen in the organization of their activity and the socio-territorial conflicts that arise in the management of a common good and the organization of the territory. Based on ethnographic work, direct observation, interviews and study of documents, different participatory mechanisms were analyzed, which show that the fishermen managed to introduce regulations that went beyond utilitarian principles and ensured the sustainability of the fishing resource. The public dimension of the institutional spaces allows to address the status of artisanal fishing and to show the existing recognition of the fishermen as valid interlocutors, even though they are subject to tensions. The results of the participatory processes have generated tools and capacities around fishing as a common good, although the coexistence of formal and informal activities, territorial privatization practices and competition of activities undermines the legitimacy of fishing as a territorial common good.
Keywords: Socio-territorial conflict; public debate; common goods; artisanal fishing; ethnography.